2014
DOI: 10.1007/s11627-014-9641-1
|View full text |Cite
|
Sign up to set email alerts
|

Induction of bulb organogenesis in in vitro cultures of tarda tulip (Tulipa tarda Stapf.) from seed-derived explants

Abstract: A protocol for obtaining bulbs via in vitro organogenesis was developed for tarda tulip (Tulipa tarda Stapf). Scale explants were obtained from bulbs formed at the base of seedlings or from adventitious bulbs that developed from callus tissue forming on stolons or on germinating seeds. Some explants were subjected to chilling at 5°C for 12 wk. The culture media contained 3 or 6% sucrose and was supplemented with either no growth regulators, either 0.5 μM 6-benzyl-aminopurine (BAP) or 18.9 or 94.6 μM abscisic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 38 publications
3
11
1
Order By: Relevance
“…As the next step for obtaining properly developed adventitious bulbs of T. kaufmanniana, we tested different combinations of cold incubation and PGRs previously shown to influence the efficiency of embryo in vitro culture of many crops (Maslanka and Bach, 2014;Uzun et al, 2014). In our experiment, germination of the embryos cultivated in vitro was observed immediately 3 days after excision, when they began to enlarge, develop the radicle and then hypocotyl ( Figure 4A-B).…”
Section: The Pathways Of Embryo Development In Vivo and In Vitromentioning
confidence: 97%
See 2 more Smart Citations
“…As the next step for obtaining properly developed adventitious bulbs of T. kaufmanniana, we tested different combinations of cold incubation and PGRs previously shown to influence the efficiency of embryo in vitro culture of many crops (Maslanka and Bach, 2014;Uzun et al, 2014). In our experiment, germination of the embryos cultivated in vitro was observed immediately 3 days after excision, when they began to enlarge, develop the radicle and then hypocotyl ( Figure 4A-B).…”
Section: The Pathways Of Embryo Development In Vivo and In Vitromentioning
confidence: 97%
“…A period of low temperature is required to interrupt the embryo dormancy, induce germination and initiate bulb primordium (Khodorova and Boitel-Conti, 2013). Furthermore, it was reported that the in vitro formation of bulblets from tulip was induced by cultivation at 20°C for 14 to 18 wk (Maslanka and Bach, 2014), while in another study the regenerated shoots were able to form bulblets only after cold treatment for 12 wk (Kuijpers and Langens-Gerrits, 1997).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…It has been reported that 3% to 6% sucrose promotes significant outgrowth of lilium bulblets cultured in vitro (Bonnier and Van Tuyl 1997;Maślanka and Bach 2014), therefore we used 6% sucrose. For the hormone treatments, three concentrations were tested in order to find the optimal dose for the experiments: 0.5, 5 and 25 μM for GR24 and 1, 25, 50 and 100 μM for BAP.…”
Section: Assessing Axillary Bud Growth In Vitromentioning
confidence: 99%
“…There are two bottleneck aspects during in vitro regeneration in tulip. First, the limited amount of competent tissues and second, that regeneration results in shoots and not in bulbs (Flavell 2009;Alderson and Rice 1983;Alderson and Taeb 1990;Baker and Wilkins 1988;Maślanka and Bach 2014;Minas 2007;Podwyszyńska 2006;Podwyszynska and Sochacki 2010;Taeb and Alderson 1990b). Young floral stalks are the most commonly used explant in tulip because they bypass the callus stage and regenerate adventitious shoots under shoot induction medium (Alderson and Taeb 1990).…”
Section: Lily Bulb Scales As a Model To Study Regeneration Recalcitramentioning
confidence: 99%